Presurgical evaluation of patients with epilepsy and normal MRI: role of scalp video-EEG telemetry. Issue 1 (1st January 1999) - Scott, C A; Fish, D R; Smith, S J M; Free, S L; Stevens, J M; Thompson, P J; Duncan, J S; Shorvon, S D; Harkness, W F J
Abstract : When considering surgery for intractable partial seizures, even with high resolution MRI, some patients do not show structural abnormalities. The aim was to consider whether these patients were likely to proceed to surgical treatment after scalp video-EEG telemetry. All patients undergoing presurgical evaluation at the National Hospital for Neurology and Neurosurgery between 1995 and 1997 were reviewed and 40 were identified without definite MRI abnormalities. None of 40 disclosed a well localised epileptogenic zone concordant with other tests that would have allowed the patient to proceed directly to surgery. In five of the 40, evaluation led to a hypothesis that could be tested by intracranial studies; three proceeded to surgery. It is suggested that high quality MRI is performed first when surgical evaluation is undertaken and if negative the patient carefully counselled before proceeding with any investigations, as successful resective surgery is an unlikely outcome in such MRI negative cases.